The characterization of borided pure niobium - Usta, M (Elsevier Science Sa, 2005)
In this study, mechanical properties of borided pure niobium were investigated. Boronizing was carried out in a solid medium consisting of Ekabor powders at 940 degrees C for 2, 4 and 8 h. The formation of NbB2 on the surface of pure niobium was confirmed by XRD analysis. Metallographic studies revealed an almost uniform and compact boride layer on the surface of the pure niobium. Experimental results showed that longer boronizing time resulted in thicker boride layers. The thickness of boride layer ranged from 8 to 22 mu m with some scatters. The hardness of borided specimens decreased with the distance from the surface to the interior of the test material. The hardness of the boride on the substrate was 2500 HV while, the hardness of the substrate was 110 HV. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: boronizing; niobium; borides; hardness; Ekabor powders